Analysis of Groundwater Quality Using Fuzzy Synthesis Evaluation (Diyala Journal of Engineering Sciences, 2009)
Thriving of the society in Zhengzhou city and development of its economy needs scientific and practical solutions of two main problems; natural water shortage and pollution. It is essential to assess the groundwater quality in order to confirm public safety in Zhengzhou and to reduce contamination in there. Fuzzy Synthetic evaluation was applied to delineate the extent of groundwater contamination in Zhengzhou. Assessment of shallow groundwater results concluded that the first three grades of Chinese water quality standards are 91%, whereas the fourth and fifth grades constitute 9% of it. For the deep water quality, the first two grades are 94% and 6%. It is deduced that part of the shallow groundwater quality is effectively contaminated. Contamination disappears going downward into the deep water. Cluster analysis show exactly same deduction. Fuzzy synthetic evaluation results (using Geographic Information System) were employed to assess the groundwater flow direction around the surveyed wells. It is concluded that infiltration of upstream industrial groundwater is probable into the deep confined groundwater